Respuestas

2012-09-17T18:07:26+02:00

quedaria: 2sen((60+20)/2)cos((60-20)/2), 2sen40cos20

cos60+cos20=2cos((60+20)/2)cos((60-20)/2)= 2cos40cos20

sen70+sen10=3sen((70+10)/2)cos((70-10)/2)=2sen40cos30

cos60+c0s10=2cos((60+10)/2)cos((60-10)/2)=2cos35cos25

resolvemos: 2sen40cos20/2cos40cos20= 2sen40/2cos40= 2tg40

2sen40cos30/2cos35cos25. 2t40-2sen40cos30/2cos35cos25

2012-09-17T20:56:05+02:00

seria entonces  2sen((60+20)/2)cos((60-20)/2), 2sen40cos20

cos60+cos20=2cos((60+20)/2)cos((60-20)/2)= 2cos40cos20

sen70+sen10=3sen((70+10)/2)cos((70-10)/2)=2sen40cos30

cos60+c0s10=2cos((60+10)/2)cos((60-10)/2)=2cos35cos25

resolvemos: 2sen40cos20/2cos40cos20= 2sen40/2cos40= 2tg40

2sen40cos30/2cos35cos25. 2t40-2sen40cos30/2cos35cos25